Psychological Detachment from School: Examining the Effects of Home Challenges on School Engagement - Arcemo, Micaella; Mirabuna, Kristine Dominique; Abuyo, Madelle Loredo (Universitas Muhammadiyah Surakarta, 2022)
This study aimed to (1) determine the participants' demographic profile, (2) identify their level of home challenges encountered, (3) identify their level of psychological detachment from school at home, (4) identify their level of school engagement, (5) identify the predictors of school engagement, and (6) determine whether psychological detachment from school at home mediated the relationship between home challenges encountered and school engagement.The researchers gathered data from 371 second and third year college students from LPU-Laguna and LPU-SC School of Health Sciences who were 18 to 24 years old using the HCES, PDS-S, and SES. Results showed that participants were mostly 20 years old, females, regular, second years, from CAM and CITHM, from lower-middle income families of about 4 to 8 members, and first-born children with 1 to 2 siblings. They exhibited moderate levels of home challenges encountered, psychological detachment from school, and school engagement. Home challenges encountered were significant predictors of school engagement. Psychological detachment from school mediated the relationship between home challenges encountered and school engagement. This study provided substantial evidence emphasizing the overlap between home and school domains.